2013
DOI: 10.1007/s10815-013-0102-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment of hydrogen-rich saline abates testicular oxidative stress induced by nicotine in mice

Abstract: Purpose The present study was designed to test the hypothesis that long-term treatment with hydrogen-rich saline abated testicular oxidative stress induced by nicotine in mice. Methods The effects of hydrogen-rich saline (6 ml/kg, i.p.), vitamin C (60 mg/kg, i.p.) and vitamin E (100 mg/kg, i.p.) on reproductive system and testicular oxidative levels in nicotinetreated (4.5 mg/kg, s.b.) mice were investigated. Results It was found that vitamin C and vitamin E attenuated serum oxidative level, but did not lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Previous studies have reported decreased gene expression of P450 cholesterol side chain cleavage enzyme (CYP11A1), 3β‐hydroxysteroid dehydrogenase (HSD) and steroidogenic factor 1 in Leydig cells exposed to nicotine in vitro (Guo et al., ) and in vivo (Jana et al., ). Apart from oxidative stress which was reported to directly cause testicular impairment and decline in spermatogenesis following nicotine exposure (Jana et al., ; Li et al., ; Mosbah et al., ), reduced circulating levels of FSH and LH may be partly responsible for the observed impairment in spermatogenesis, thus suggesting an extra‐testicular mechanism. Considering the fact that FSH and LH are extra‐testicular hormones, it is likely that the stressors impaired pituitary function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported decreased gene expression of P450 cholesterol side chain cleavage enzyme (CYP11A1), 3β‐hydroxysteroid dehydrogenase (HSD) and steroidogenic factor 1 in Leydig cells exposed to nicotine in vitro (Guo et al., ) and in vivo (Jana et al., ). Apart from oxidative stress which was reported to directly cause testicular impairment and decline in spermatogenesis following nicotine exposure (Jana et al., ; Li et al., ; Mosbah et al., ), reduced circulating levels of FSH and LH may be partly responsible for the observed impairment in spermatogenesis, thus suggesting an extra‐testicular mechanism. Considering the fact that FSH and LH are extra‐testicular hormones, it is likely that the stressors impaired pituitary function.…”
Section: Discussionmentioning
confidence: 99%
“…, ; Simoni, Bakker, & Krausz, ; Rinaldi, Fontani, Aravagli, & Saragò, ) impair fertility, the level of exposure of young adult men of childbearing age to stress and nicotine is on the increase. Several reports have linked stress‐ and nicotine‐induced reproductive impairment to oxidative stress (Jana, Samanta, & De, ; Li, Lu, Zhang, & Zhang, ; Mosbah, Yousef, & Mantovani, ). Vitamin E is one of the antioxidants used over the years for management of male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Since the hydrogen molecule is electrically neutral and considerably smaller than other antioxidants, it can easily penetrate membranes and enter organelles (12,26); however, it remains unclear exactly what type of oxidative stress is involved in femoral head necrosis. GSH stabilizes the lysosomal membranes to suppress injury to the vascular endothelium.…”
Section: A B a B Discussionmentioning
confidence: 99%
“…Hydrogen has a positive effect in inhibiting oxidative stress. Hydrogen gas is flammable, explosive and difficult to store and use; however, hydrogen gas-saturated saline, also known as hydrogen-rich saline, is safe, economical and easily available, and is universally employed in medicine (12,13). Injecting hydrogen-rich saline into the intraperitoneal cavity is an easy and effective method that can be readily adapted for potential clinical practice (14).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis can seriously affect reproductive function of normal testes. Nicotine is also reported to enhance the synthesis of cholesterol, triglycerides, phospholipids and free fatty acids in the testes and increase peroxidative damage (Li, Lu, & Zhang, ). On the other hand, statins are prescribed to reduce hyperlipidaemia (Tobert, ).…”
Section: Introductionmentioning
confidence: 99%